On the Role of Musical Ekphrasis in A.F. Losev’s Novel Tchaikovsky Trio - Giorgia Rimondi (Studia Litterarum)
The article examines the concept of “musical ekphrasis” in literature and its reflection in A.F. Losev’s prose. Although ekphrasis is usually defined as a verbal description of visual representation, scholars have recently argued that there is also a “musical ekphrasis.” While traditional ekphrasis is based on the ontological duality of the verbal and the visual, musical ekphrasis adds a third intermediate level to this: music is expressed through its visualization. The author analyzes the descriptions of musical works in the A.F. Losev’s novel Tchaikovsky Trio (1933), where the musical form reveals visual or spiritual content, symbolizing the inner life of the main character. Different references to music can be found in the novel, and most of the novel is in fact devoted to this. Ekphrasis can be expressed as brief of a musical fragment, description of spiritual movements (the descriptive and narrative topos of romantic-symbolic origin), the disclosure of the semantic essence of a musical work, the metaphorization of reality through music (parallel between the Trio and the relationship of the main character and the pianist), or the spatialization of music. Through ekphrasis Losev portrays two opposing worlds living side by side in harmony: love and suffering (as in Rakhmaninov’s aria Francesca da Rimoni), chaos and order (in Beethoven’s sonata), man’s desire to understand the inner meaning of life, the antithesis of will and destiny (in Tchaikovsky Trio).